Letters. - Russell, Rand; Aquin, Creighton (Architectural Record, 1985)
Presents letters to the editor referencing articles and topics discussed in previous issues. Reaction to the proposed desecration of the Whitney by architect Michael Graves; Information on computer-aided drafting and specification writing.